Deciphering the interplay of extracellular vesicles and drug resistance in HER2-positive breast cancer: insights, biomarkers and therapeutic implications - Martinez Pacheco, Sarai (Trinity College Dublin. School of Pharmacy & Pharma. Sciences. Discipline of Pharmacy, 2023)
According to a World Health Organisation (WHO) report on 3rd March 2021, breast cancer is the most common form of cancer in the world and the leading cause of cancer death among females. In 2020, 2.26 million newly breast cancer patients were diagnosed (11.7% of all cancers) and approximately 685 000 died worldwide from this disease. The same year, 576,337 new breast cancers were diagnosed in WHO Europe countries with 157,111 predicted deaths in both sexes. In Ireland, there are 3,433 females diagnosed with breast cancer per year (23.8% of all invasive cancers) with 745 deaths per year (15.2% of all cancer deaths), making breast cancer the second most common cause of cancer deaths. Breast cancer cannot be considered as a single disease due to the high heterogeneity. This type of cancer includes distinct subtypes associated with different clinical outcomes. Understanding this heterogeneity is fundamental for the development of targeted personalised medicine and therapeutic intervention. Over-expression of human epidermal growth factor receptor 2 (HER2) occurs in ~ 20% of breast cancers and confers aggressive behaviour and poorer prognosis. Thankfully, several drugs such as trastuzumab, lapatinib, pertuzumab, and neratinib have been developed to target HER2, potentially providing substantial benefit for many patients. Despite the development of HER2-targeted therapies which have improved the survival outcomes for HER2- positive breast cancer patients, it is estimated that up to 70% of patients with HER2-overexpressing tumours do not gain benefit, because of innate-, acquired- and cross-resistance to HER2-targeted therapies; the main reason for which these drugs fail in the clinic. Further investigations and continued efforts are required to unravel the main effectors of resistance to predict the outcome of treatments and offer more therapeutic options to a wide range of patients. Extracellular vesicles (EVs) are a heterogenous group of cell-derived membranous structures present in biological fluids and involved in multiple physiological and pathological processes. Nowadays, EVs are considered an additional mechanism for intracellular communication, and it is essential to comprehend the cellular processes implicated in their biology to understand their physiological and pathological functions, as well as clinical applications involving their use and/or analysis. However, in this expanding field, much remains unknown regarding the origin, biogenesis, secretion, targeting, and future applications of these vesicles. Previous research performed by our group and others has shown that EVs are involved in transmitting resistance, and it demonstrated that EVs induced previously drug-sensitive cells to become drug-resistant. Specifically in cancer, EVs can act as intercellular mediators in tumorigenesis mechanisms including the transmission of resistance to anti- cancer drugs, angiogenesis, metastasis, and immunosuppression. Furthermore, there is evidence suggesting that EVs might bind drugs such as trastuzumab, reducing bioavailability of the drug to its receptor (HER2) on cancer cells. Due to that, EVs may be substantially inhibiting cancer patients gaining benefit from anti-cancer drugs. This project aims to understand the transmission of resistance to anti-cancer drugs through EVs, investigate neratinib-resistance mechanisms in HER2+ breast cancer, and discover new pathways and biomarkers associated with neratinib resistance, ultimately benefiting cancer patients. The project involves various objectives such as comparing EVs separation methods, analysing proteome profiles of neratinib-sensitive and neratinib-resistant cells, EVs characterisation derived from neratinib-sensitive and neratinib-resistant breast cancer cell lines, studying hypoxia's influence, evaluating a 3D cell culture model, surveying in vitro models in cancer research, and examining the effect of tucatinib on EVs? release in breast cancer cell lines. Thus, this project started by evaluating the importance of comparing EVs separation methods using multiple sources of conditioned medium (CM) to ensure accurate and generalisable results by comparing two different EVs separation methods: differential ultracentrifugation (dUC) and polyethylene glycol (PEG) precipitation followed by ultracentrifugation (PEG+UC). We found that different cell lines and separation methods resulted in variations in EVs characteristics, such as size, quantity, and protein content. Although both approaches showed to be reproducible methods for obtaining pure EVs, the inclusion of multiple CM sources is crucial for meaningful comparisons and generalisability of results across samples. Additionally, we also aimed to explore the proteomic differences between HER2-positive breast cancer cell lines and their neratinib-resistant counterparts developed in our group previously. We discovered that neratinib-resistant cell lines HCC1943 NR and SKBR3 NR, which are HER2+ER-, exhibited significantly lower expression of AGR2 compared to their neratinib-sensitive counterparts. Conversely, the luminal B breast cancer cell lines (HER2+ER+) EFM192A and EFM192A NR did not show the same pattern of AGR2 expression. Notably, the overexpression of AGR2 in ER-positive breast cancer has been linked to a poor prognosis, particularly in hormone therapy-resistant tumours. Therefore, the next logical step was to investigate the role of AGR2 down-regulation in the aggressiveness of neratinib-resistant HER2+ breast cancer cell lines. For that, we performed functional assays after transfecting AGR2 into neratinib-resistant cells. The results showed that AGR2 transfection led to changes in cell migration, invasion, anoikis-resistance, and neratinib-resistance, as well as some alterations in the expression of EMT markers and HER2. We also evaluated in this project how neratinib-resistance can affect EVs? release and EVs? cargo in both normoxia and hypoxia conditions and by using different EVs separation approaches. We found that neratinib-resistant cell line variants release fewer EVs compared to their neratinib-sensitive counterparts in both normoxia and hypoxia. In addition, those EVs derived from neratinib-resistant cell lines carried less HER2 than their neratinib-sensitive counterparts. The results obtained under hypoxic conditions indicated that hypoxia modified the release and content of EVs in a manner specific to each cell type, which could potentially impact the invasiveness of breast cancer cells and their resistance to drugs. We also investigated the suitability of two different 3D-culture platforms to collect EVs and to include 3D cell culture in this comparison. We also performed the first worldwide survey about the existing pre-clinical in vitro models currently employed in cancer research. Finally, we investigated whether exposure to a low dose of tucatinib, taking into consideration limitations in achievable dosage of anti-HER2 therapies due to factors such as tumour size, location, and heterogeneity, could inadvertently lead to increased HER2 expression and/or release of EVs, potentially promoting tumour aggressiveness. We demonstrated that neratinib-resistance conferred cross-resistance to tucatinib in all three HER2+ breast cancer cell lines studied and that HCC1954 cells manifest innate resistance to tucatinib. The analysis of CM collected after tucatinib treatment showed a higher abundance of CD9+ and HER2+ events compared to their untreated counterparts, with significant differences observed in CM obtained from HCC1954 cells. In conclusion, this research demonstrates that neratinib-resistant cell lines exhibit distinct proteomic profiles and altered EVs? release compared to their neratinib-sensitive counterparts in both normoxic and hypoxic conditions. Notably, an increased presence of E-cadherin, IL-6, IL-8, and HER2 was detected in EVs derived from HER2+ cancer cells under hypoxia. These changes in EVs? cargo composition have the potential to impact tumour progression and contribute to resistance against anti-HER2 therapies.
APPROVED
Keywords: Breast Cancer; Extracellular Vesicles; Neratinib-resistance; Hypoxia; 3D cell culture